Cuffed vs. uncuffed tracheal tubes in children: a randomised controlled trial comparing leak, tidal volume and complications - Chambers, N.; Ramgolam, A.; Sommerfield, D.; Zhang, Guicheng; Ledowski, T.; Thurm, M.; Lethbridge, M.; Hegarty, M.; von Ungern-Sternberg, B. (Wiley-Blackwell, 2018)
© 2017 The Association of Anaesthetists of Great Britain and Ireland Cuffed tracheal tubes are increasingly used in paediatric anaesthetic practice. This study compared tidal volume and leakage around cuffed and uncuffed tracheal tubes in children who required standardised mechanical ventilation of their lungs in the operating theatre. Children (0–16 years) undergoing elective surgery requiring tracheal intubation were randomly assigned to receive either a cuffed or an uncuffed tracheal tube. Assessments were made at five different time-points: during volume-controlled ventilation 6 ml.kg -1 , PEEP 5 cmH 2 O and during pressure-controlled ventilation 10 cmH 2 O/ PEEP 5 cmH 2 O. The pressure-controlled ventilation measurement time-points were: just before a standardised recruitment manoeuvre; just after recruitment manoeuvre; 10 min; and 30 min after the recruitment manoeuvre. Problems and complications were recorded. During volume-controlled ventilation, leakage was significantly less with cuffed tracheal tubes than with uncuffed tracheal tubes; in ml.kg -1 , median (IQR [range]) 0.20 (0.13–0.39 [0.04–0.60] ) vs. 0.82 (0.58–1.38 [0.24–4.85]), respectively, p < 0.001. With pressure-controlled ventilation, leakage was less with cuffed tracheal tubes and stayed unchanged over a 30-min period, whereas with uncuffed tracheal tubes, leakage was higher and increased further over the 30-min period. Tidal volumes were higher in the cuffed group and increased over time, but in the uncuffed group were lower and decreased over time. Both groups showed an increase in tidal volumes following recruitment manoeuvres. There were more short-term complications with uncuffed tracheal tubes, but no major complications were recorded in either group at long-term follow-up. With standardised ventilator settings, cuffed tracheal tubes produced better ventilation characteristics compared with uncuffed tracheal tubes during general anaesthesia for routine elective surgery.